Amberene and 1-methylamberene, isolated and identified from Kuji amber (Japan). (June 2018) - Kawamura, Tetsuaki; Koshino, Hiroyuki; Nakamura, Takemichi; Nagasawa, Yoshiyuki; Nanao, Hidetaka; Shirai, Masayuki; Uesugi, Shota; Ohno, Misa; Kimura, Ken-ichi
Abstract: Abundant labdatriene derivatives, named amberene [15, 19, 20-trinor-5, 7, 9-labdatriene (or 1, 6-dimethyl-5-isopentyltetralin) (1 )] and 1-methylamberene [15, 20-dinor-5, 7, 9-labdatriene (or 1, 1, 6-trimethyl-5-isopentyltetralin) (2 )] were isolated from the methanol extract of Kuji amber by HPLC. The structures were elucidated by spectral analyses including EIMS, 1D and 2D NMR and some previous assignments corrected.